Microplastic abundance from pig farm effluent and surface water in Sungai Tuang, Melaka, Malaysia - Suwanty Ridzuan Anoam; Muhammad Farid Abdul Hakim Lim; Mohamad Hafiz Abdul Halim; Shamsuri Abdul Manan; Masni Mohd Ali; Khairiatul Mardiana Jansar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Livestock is one of the country’s important economic resources, nevertheless, an unsystematic livestock farm management system contributes to microplastic pollution. Microplastics (MPs) pollutant hurts the environment and human life, limited studies have been done in Malaysia’s freshwater ecosystems. Therefore, this research was to determine the abundance of MPs in surface water and sediments from the nearby river and the last catchment pond of pig farm effluent in Paya Mengkuang and Sungai Tuang, Melaka. The concentration of MPs was compared with six water quality parameters (pH, biochemical oxygen demand (BOD), suspended solids (SS), dissolved oxygen (DO), total ammoniacal nitrogen (NH3-N), and chemical oxygen demand (COD). This study found that the average concentration of MPs was 487.38 particles/L and 50.96 particles/g for water and sediment samples consequently. This study showed a significant correlation between COD concentration and microplastic count in sediment samples. The source of microplastics in rivers is associated with anthropogenic activities such as unsystematic garbage disposal and poultry manure. The prevalence of microplastics in the environment of MPs could threaten the safety of resource utilization as MPs enter the food chain in aquatic ecology and pose a severe threat to aquatic organisms directly and subsequently to humans. Our study provides essential data on microplastic pollution in river estuaries and livestock farm areas.